Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya di PGMI 3 UINSU - Matondang, Aflah Husnaini; Wandini, Rora Rizky (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Misconceptions can be defined as a situation where someone has a certain concept. Misconceptions can arise in students because they do not understand the concept of the question clearly, so that students will have difficulty solving the problem they are solving. Difficulties often arise when someone makes mistakes in the stages of solving the problem. This type of research is descriptive research with a qualitative approach. Descriptive research is used to see and describe current problems or facts that are revealed without any manipulation. This research aims to describe misconceptions in working on flat shape problems using polya theory that occur among PGMI 3 UIN North Sumatra students. The results of the research and discussions carried out show that there are several misconceptions, namely, (1) At the understanding stage it is not clear what is known whether it is a triangle or a square when writing the base and height, (2) At the implementation stage there is a lack of signs or units of Cm in L = 1/2. 8 x 6 = L = 24 It should be written like this L=1/2.8cm x 6cm = L = 24 cm, (3) In the assessment results there is also a lack of cm marks. (4) In this answer, there is a lack of writing points in the four stages contained in the polya theory, such as the absence of writing on understanding, planning, implementation and assessment, (5) There is a mistake at the assessment stage, namely that there are no sentences in the sentence written only the result alone is 40 cm. At this stage you should write a sentence like this, So the area of the rectangle = 40 cm. Therefore, it is hoped that this misconception will not happen again to PGMI 3 students or other students